The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7717/peerj.9315
|View full text |Cite
|
Sign up to set email alerts
|

Plastid genomes of the North American Rhus integrifolia-ovata complex and phylogenomic implications of inverted repeat structural evolution in Rhus L.

Abstract: Plastid genomes (plastomes) represent rich sources of information for phylogenomics, from higher-level studies to below the species level. The genus Rhus (sumac) has received a significant amount of study from phylogenetic and biogeographic perspectives, but genomic studies in this genus are lacking. Rhus integrifolia and R. ovata are two shrubby species of high ecological importance in the southwestern USA and Mexico, where they occupy coastal scrub and chaparral habitats. They hybridize frequently, represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…pubescens, indicating that gene deletion occurred during cp evolution. The missing rps19 gene from the cp genomes was also reported in some species in Rhus (Barrett, 2020). Some lost genes were proved to be transferred to the nuclear or mitochondrial genomes, where they may still be expressed (Daniell et al, 2016).…”
Section: Divergence Time Datingmentioning
confidence: 71%
See 1 more Smart Citation
“…pubescens, indicating that gene deletion occurred during cp evolution. The missing rps19 gene from the cp genomes was also reported in some species in Rhus (Barrett, 2020). Some lost genes were proved to be transferred to the nuclear or mitochondrial genomes, where they may still be expressed (Daniell et al, 2016).…”
Section: Divergence Time Datingmentioning
confidence: 71%
“…Over the past years, it has been used to elucidate plant molecular evolution, enhancing our understanding of chloroplast biology, conservation, and diversity (Daniell et al, 2016 ). Moreover, cp genomes represent rich information sources for phylogenomics, from higher‐level to below the species level (Barrett, 2020 ; Dong et al, 2021 , 2022 ; Ruhfel et al, 2014 ). To date, the cp genome is available for only one representative Cotinus species.…”
Section: Introductionmentioning
confidence: 99%
“…Barrett et al (2020) found the loss of rps19 and rpl22 genes from the chloroplast genome of R. chinensis (accession No. MG267385) [ 49 ], while the two genes were annotated in our current study. With the acquisition of the new complete chloroplast genome of R. chinensis , more complete genomic information indicated that the rps19 gene was present in the R. chinensis sample and that there were some minor differences in its location compared to other Rhus species.…”
Section: Resultsmentioning
confidence: 99%